Símbolos, ritos e identidades en la parada del gallardete en el distrito de Huamachuco – provincia Sánchez Carrión – 2017. - Rojas Rodríguez, Manuel Anthony (2018)
SYMBOLS, RITES AND IDENTITIES AT THE PENNANT STOP IN THE DISTRICT OF HUAMACHUCO – PROVINCE THE SANCHEZ CARRION – 2017, aims to explain a social fact that marks transcendence for Huamachuco a ditrict settled in the andes of the Region La Libertad in the north of Peru. The event of marked transcendence and sociocultural continuity unites and motivates multiples identities among rural people of the homestead a city from Huamachuco. The symbolic stregth of each participant gives the Wood, the land and the banner, forces certain ritual, motivating diverse identities. Three important rites define the pennant stop in Huamachuco: the cutting of the Wood, the transfer an de stop in the main square.